Prioritizing Information Sources and Requirements in Students' Choice of Higher Education Destination: Using AHP Analysis - Erdil, Damla Urer; Tumer, Mustafa; Nadiri, Halil; Aghaei, Iman (Sage Publications Inc, 2021)
Attracting and enrolling international students have become the primary concern of marketing efforts of higher education institutions. For this purpose, understanding the decision-making process of students is vital. This study examines the information sources, requirements, and choice factors of international students who study their higher education in an emerging higher education destination. This study is conducted through a quantitative approach, based on both exploratory factor analysis (EFA) and the analytic hierarchy process (AHP). A survey was conducted with students who enrolled at a state university for the first time. University websites are identified as the most used sources of information. According to the study's findings, job and scholarship opportunities are identified as the first and most crucial concern of international students. This study is of particular significance for higher education institutions in emerging higher education destinations to better understand students' decision-making process.
Keywords: international students; destination choice; higher education; information requirements; information sources; analytic hierarchy process (AHP)